2022
DOI: 10.1371/journal.pbio.3001289
|View full text |Cite
|
Sign up to set email alerts
|

Metacommunity analyses show an increase in ecological specialisation throughout the Ediacaran period

Abstract: The first animals appear during the late Ediacaran (572 to 541 Ma); an initial diversity increase was followed reduction in diversity, often interpreted as catastrophic mass extinction. We investigate Ediacaran ecosystem structure changes over this time period using the “Elements of Metacommunity Structure” framework to assess whether this diversity reduction in the Nama was likely caused by an external mass extinction, or internal metacommunity restructuring. The oldest metacommunity was characterised by taxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 68 publications
0
28
0
Order By: Relevance
“…The 'Elements of Metacommunity Structure' framework used here is a hierarchical analysis that identifies properties in site-byspecies presence/absence matrices that are related to the underlying processes, such as species interactions, dispersal, and environmental filtering that shape species distributions 10 . Application to various marine and terrestrial palaeocommunities has demonstrated the robustness of these methods to fossil data and sample size variations 13,14 . There are fourteen different types of metacommunity structure which are determined by the calculation of three metacommunity metrics: Coherence, Turnover, and Boundary Clumping, which reveal different controlling processes of underlying metacommunity structure 10,[15][16][17][18] .…”
mentioning
confidence: 99%
“…The 'Elements of Metacommunity Structure' framework used here is a hierarchical analysis that identifies properties in site-byspecies presence/absence matrices that are related to the underlying processes, such as species interactions, dispersal, and environmental filtering that shape species distributions 10 . Application to various marine and terrestrial palaeocommunities has demonstrated the robustness of these methods to fossil data and sample size variations 13,14 . There are fourteen different types of metacommunity structure which are determined by the calculation of three metacommunity metrics: Coherence, Turnover, and Boundary Clumping, which reveal different controlling processes of underlying metacommunity structure 10,[15][16][17][18] .…”
mentioning
confidence: 99%
“…Considering that, even for some well-studied taxonomic groups, the current rates of extinction are unknown or seem to have been substantially underestimated [3,4], global biodiversity is in jeopardy.A cursory survey of biodiversity-related papers that have been published in the journal in the past year reveals several principal topics. In this issue alone, we feature work addressing the biodiversity of marine communities half a billion years apart [5,6] and the use of artificial intelligence to automate the surveillance of threatened species [3].Across the past year, one topic to emerge has been how biodiversity has changed in the past, with papers attempting to infer what forces, both biotic and abiotic, have driven these changes, often with the implicit or explicit expectation that we can learn lessons about future change. These papers include (in roughly temporal order) studies of ancient Ediacaran animal communities [5], end-Cretaceous sharks [7], Cenozoic snakes [8], and cold-water corals over the past 20,000 years [6] (Fig 1).…”
mentioning
confidence: 99%
“…A cursory survey of biodiversity-related papers that have been published in the journal in the past year reveals several principal topics. In this issue alone, we feature work addressing the biodiversity of marine communities half a billion years apart [5,6] and the use of artificial intelligence to automate the surveillance of threatened species [3].…”
mentioning
confidence: 99%
See 2 more Smart Citations